1980
DOI: 10.1037/h0077690
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in aging normal and neonatally androgenized female rats.

Abstract: Decline in reproductive success was compared in normal and neonatally androgenized female rats permitted to receive 1 or 5 ejaculations during each of 7, 5, 3, or 1 mating test Exposing the females to .5 ng of testosterone propionate on Day H of life increased their age-related rate of decline in the number of successful pregnancies and offspring born in each litter as well as in behavioral receptivity In both normal and neonatally androgenized animals, fertility and receptivity were greater in animals receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In agreement with previous reports (Davis et al 1977;Gerall et al 1980), we found that the intromittent requirements for pregnancy were greater for aged compared with those for young rats. For those old/cyclic animals which received a low number of intromissions, reproductive failure was associated with an absence of nocturnal prolactin surges (such surges were detected in only one out of four animals at day 3).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with previous reports (Davis et al 1977;Gerall et al 1980), we found that the intromittent requirements for pregnancy were greater for aged compared with those for young rats. For those old/cyclic animals which received a low number of intromissions, reproductive failure was associated with an absence of nocturnal prolactin surges (such surges were detected in only one out of four animals at day 3).…”
Section: Discussionsupporting
confidence: 94%
“…In PVO, ovulation does not occur spontaneously despite the presence of well-developed follicles (Meites et al 1978). In contrast to the young female, rats of 9-10 months of age exposed to only one ejaculation during mating do not readily become pregnant and exhibit plasma concentrations of progesterone similar to those of unmated controls (Davis, Gray & Dewsbury, 1977;Gerall, Dunlap & Sonntag, 1980). However, reasonably high pregnancy rates and plasma levels of progesterone after mating are observed for those aged females mated until three or five ejaculations have occurred.…”
Section: Introductionmentioning
confidence: 56%
“…In social species, such as sheep, higher rank usually results in females gaining access to better or more food, and thereby allows the production of larger, healthier and perhaps more offspring, as has been documented in other ruminant species [39,40] and primates [41]. However, there may be an overall trade-off, in that prenatal exposure resulting in mild masculinization may cause an early decrease in fertility, as evidenced by studies in the androgenized female rat [42].…”
Section: Chronic Estradiol Exposure Effects On Reproductionmentioning
confidence: 92%
“…Both the SDN and AVPV are thought to play a role in the display of male sex behaviors (Rhees et al, 1999; Roselli et al, 2004), and lesion studies have demonstrated the critical importance of the AVPV in generating the preovulatory gonadatropin surge in females (Gerall et al, 1980; Wiegand and Terasawa, 1982). Although still highly controversial, in humans and sheep, a smaller SDN volume has been linked to the defeminization of sexual behavior and mate choice in males (Roselli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%